PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP PRESTASI KERJA KARYAWAN PADA DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KABUPATEN AGAM - SUSANTI, WARNA; NATASSIA, RIZKY; UTAMI, HAYU YOLANDA (Pendidikan Ekonomi, 2013)
ABSTRACTThis study aims to reveal: 1) How does the influence of job satisfaction on employee performance Transport Department of Communication and Information Agam; 2) How does organisasit commitment on employee performance Transport Department of Communication and Information Agam; 3) How does the influence of job satisfaction and organisasit commitment Â on performance Department of Transportation employee Agam Communications and Information Technology.Object of study is the Department of Transportation employee Agam Communication and Information. The study population was all employees of the Department of Communication and Information Agam numbering 70 people. The data analysis technique used is multiple regression.Results of the study are: 1) There is a positive and significant effect between job satisfaction on job performance at the Department of Communication and Information Agam with regression coefficient 0.206. Means to increase employee performance can be done by improving the job satisfaction at the Department of Communication and Information Agam, 2) There is a positive and significant effect between organizational commitment on job performance at the Department of Communication and Information Agam with regression coefficient 0.109. Means to increase employee performance can be done by improving the organizationâs commitment to the Department of Transportation, Communication and Information Agam. To achieve high performance, the employee job satisfaction and organizational commitment of employees in Agam District should be improved.Â Keyword: Job Satisfaction, Organisasit Commitment, Employee Performance multiple regression.